Psychosocial Variables That Predict Chronic and Disabling Tinnitus: A Systematic Review - Kleinstäuber, Maria; Weise, Cornelia (Springer Science and Business Media Deutschland GmbH, 2021)
To improve tinnitus management we have to gain more knowledge of factors that explain how a persistent distressing tinnitus develops. The central aim of this systematic review was to identify longitudinal studies that investigated psychosocial variables predicting the transition from an acute to a chronic, disabling tinnitus (i.e. tinnitus decompensation) or tinnitus outcomes in chronic tinnitus sufferers. We conducted a systematic literature search of electronic databases and searched manually reference lists. We identified 16 eligible studies: Four longitudinal studies targeted predictors of the transition from acute to chronic tinnitus and 12 longitudinal studies investigated predictors of tinnitus distress (k = 9 observational, longitudinal studies; k = 3 ecological momentary assessment [EMA] and diary studies). The results of this systematic review showed that tinnitus distress, general psychological distress, tendencies to somatize, tinnitus-related delay of sleep onset, certain health behaviors, general illness coping, and certain personality traits (e.g. neuroticism) predicted the transition from acute to chronic, disabling tinnitus. General psychological, mental disorders, tinnitus distress, tinnitus disability (e.g. in different domains of physical, emotional, and social functioning; sleep disturbances), certain health behaviors (e.g. physical exercise), the level of physical and social functioning, and the report of other somatic problems such as pain were predictors of tinnitus outcomes in chronic tinnitus patients at a later follow-up. Studies that examined psychosocial variables as predictors of tinnitus distress are rare and had substantial methodological shortcomings. Future research should focus on core outcome domains and use standardized outcome measures to improve the comparability of results from different studies. Numerous psychosocial variables that have already been investigated as correlates of tinnitus sufferers’ functioning in cross-sectional studies are worth investigating with longitudinal designs in future research. Identified predictors of the transition from acute to chronic, disabling tinnitus have to be addressed by health care practitioners who commonly function as the first contact person of individuals with acute tinnitus in the healthcare system.
CRIS-Team Scopus Importer:2024-03-27
Keywords: Disability; Distress; Ecological momentary assessment; EMA; Longitudinal; Predictor; Psychosocial; Tinnitus